Anti-Bacterial Activity of Different Honey Samples against Bacteria Isolated from Clinical Sources (Tribhuvan University Journal of Microbiology, 2023)
Objectives: To evaluate the antibacterial activities of different honey samples against clinically isolated bacteria and also to compare the antibacterial activity of honey with standard antibioticsMethods: A study was conducted to evaluate the potent attributes of eight distinct types of honey against five pathogenic bacteria which were collected from Bharatpur Hospital of Chitwan. The susceptibility of isolates to honey was evaluated using the Agar well diffusion method. In addition, the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the effective honey samples were determined using tube macro-dilution method. MIC represents the lowest concentration at which visible inhibition of bacterial growth occurs, offering insights into the honey’s inhibitory potential. Furthermore, MBC, determined by sub-culturing the non-turbid wells from the MIC assay, elucidates the minimal concentration required for complete bactericidal activity.Results: Among the eight types of honey processed, Rudilo honey exhibited remarkable effectivity against Escherichia coli and Staphylococcus aureus, with zone of inhibition of 39 mm and 36 mm, respectively. Conversely, Manuka and Chiuri displayed heightened efficacy against Klebsiella pneumoniae with zone of inhibition 34 mm) and Proteus vulgaris (38 mm). Among the tested bacteria, Pseudomonas aeruginosa demonstrated notable resistance to all honey samples except Rudilo, Manuka, and Multiflora. Furthermore, Manuka and Rudilo exhibited the lowest MIC (6.25% v/v) against Proteus vulgaris and Staphylococcus aureus, while Rudilo displayed the lowest MBC (25% v/v) against the same pathogens. However, Chiuri presented the highest MIC and MBC against the tested bacteria. It was found that honey samples showed a greater zone of inhibition than antibiotics used against Escherichia coli, Proteus vulgaris, Klebsiella pneumoniae, and Staphylococcus aureus but for Pseudomonas aeruginosa antibiotics were found to be more effective than sampled honey.Conclusion: The study revealed that honey exhibited antibacterial properties even at its minimum inhibitory concentration (MIC), showcasing effectiveness against infections caused by Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae and Proteus vulgaris. However, its efficacy in treating infections attributed to Pseudomonas aeruginosa might be limited.